Pola Distribusi Tumbuhan Lamun di Perairan Pantai Sejuk Kabupaten Lombok Utara dalam Upaya Pengembangan Modul Ekologi - Rohmatulloh, Aulia (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2023)
Seagrass plays an important role in the life of living things. However, the existence of seagrasses in every area is damaged due to pollution and human activities. One of the areas where seagrass has not been studied is Sejuk Beach Waters in North Lombok Regency. This study aims to determine the types of seagrass, dominating species population, population density, distribution pattern, diversity of seagrass, and development of ecological modules. The type of research used is descriptive exploratory, with data collection techniques namely observation and documentation. Data analysis techniques used include: 1) diversity index; 2) dominance index; 3) population density; 4) moricita index; and 5) test the validity of the module. Based on the results of the study it was found that there were 4 types of seagrass in Sejuk Beach Waters, North Lombok Regency, namely; Enhalus acoroides, Syringodium isoetifolium, Cymodocea rotundata, and Halophila minor. The population of seagrass species that dominates the highest is found at station III of 0.2476, the population of seagrass species that dominates at each station is Syringodium isoetifolium. The highest population density was found at station I with a value of 47.1, but the one with the highest population density was Syringodium isoetifolium. The highest seagrass distribution pattern was found at station III with an Id value of 2.9608, the seagrass that had the highest Id value was Syringodiun isoetifolium. The highest diversity of seagrass species was found at station I with an H' value of 0.3637, but the one with the highest diversity was Cyromocea rotundata. Meanwhile, the seagrass that grew the lowest at each observation station was Enhalus acoroides. The results of the study were then made in the form of modules and validated by 3 experts, scores obtained from content/content experts were 80%, linguists were 86%, and visual experts were 90%, these scores stated that the developed module was valid. Then it was tested for readability on 20 students of the Biology Education Study Program, FSTT, Mandalika University of Education semester IV, the scores obtained ranged from 80% -96%, indicating that the developed module was highly legible.